The Effect of the Reverse of the Expectations in Creating Irony in Oscar Wilde's: The Importance of Being Earnest - Al Samaraie, Enas Muhammad Salih (جامعة النيلين - إدارة البحوث والتنمية والتطوير, 2017)
Very often, we resort to the easy answer expecting this and exceeding that. We expect the reaction of each character the solution of every single matter and the face of the end. Even in comedy, we have to admit, the source of every unconscious smile at the begging of reading or watching it, is the expectation of pleasure and it is on this very point comedy and Oscar Wilde play their game. But why necessarily comedy and specifically Wilde, the answer would be the issue of this study.
Keywords: الكوميديا ​​الهزلية -- الاختراق الفكري -- الفنون المسرحية -- الأدب الساخر -- وايلد، أوسكار فينغال أوفلاهرتي، ت. 1900 م